FORMULATION OF NANOSTRUCTURED LIPID CARRIERS LOADED WITH PACAR AIR HERB ETHANOL EXTRACT (IMPATIENS BALSAMINA L.) TO ENHANCE ANTIINFLAMATORY ACTIVITY IN DERMATITIS - Dirga Mega Buana, Komang
The pacar air plant (Impatiens balsamina L.) is widely cultivated in Bali dan possesses antipruritic, anti-irritant, dan anti-inflammatory activities. However, the direct use of balsam plant extract to reduce inflammation symptoms has shown less favorable results. This study aims to develop a Nanostructured Lipid Carrier (NLC) containing ethanol extract of balsam herb (NLC-IBE) dan to determine its anti-inflammatory activity both in vitro dan in vivo. NLC-IBE was prepared using an optimized high shear homogenization and ultrasonication method based on Box-Behnken Design variables: total lipid concentration, probe ultrasonication time, dan ultra turrax homogenization speed. The in vitro anti-inflammatory activity study was conducted by testing the inhibition of Bovine Serum Albumin (BSA) denaturation. Additionally, the in vivo anti-inflammatory activity was tested on an allergic contact dermatitis (ACD) animal model induced by 2,4-dinitrofluorobenzene (DNFB). The optimal NLC-IBE formulation consisted of 0.5% (w/v) IBE, a combination of black cumin oil dan stearyl alcohol (4:6) at 3.75% (w/v), Span®20 : Plantacare® 1200 surfactants (4:1) at 5% (w/v), homogenized at 6600 rpm for 8 minutes, dan probe ultrasonicated at 70% for 5 minutes. The optimal NLC-IBE formulation resulted in particle size, polydispersity index, entrapment efficiency, dan zeta potential of 194.47 ± 7.96 nm, 0.24 ± 0.01, 94.92 ± 0.99%, dan -40.78 ± 4.73 mV respectively, with spherical or oval morphology dan stability over 28 days at 4°C. In vitro drug release tests showed that lawson release from the optimal NLC-IBE formulation followed a biphasic pattern with a cumulative release of 71.043 ± 1.46% over 24 hours. The IC50 value of the optimal NLC-IBE in the BSA denaturation inhibition test was 109.56 ± 3.95 µg/mL. In vivo, NLC-IBE showed erythema scores (0.57 ± 1.13 mm), ear thickness (0.25 ± 0.01 mm), and skin moisture percentage (37.24 ± 2.90%) in the ACD animal model significantly (p value < 0.05) compared to ethanol extract of henna herb on the 4th day of observation after drug administration. Overall, the optimized NLC-IBE produced can enhance the anti-inflammatory activity of the ethanol extract of henna herb (IBE).